Situation Report: Czechoslovakia, 22 October 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Message from the Border Reykjavik: The View from Prague Charter 77 and the Copenhagen Peace Congress The Prague Vicar-General Dies The 1986 Harvest / by Frank Pohl A Difficult Ecological Recovery A Welfare State Devalued